THE ONLINE LEARNING PROCESS DURING THE COVID-19 PANDEMIC - Fina Damayanthi; Maya Rahmawati (IKIP Siliwangi, 2022)
Covid-19 makes all activities that require face-to-face turn into online, including learning activities. During this pandemic, all face-to-face learning activities are required to turn into virtual classes. This makes educators and students use online media to maximize learning activities, one of which is through media such as Zoom Cloud Meeting, Google Meeting, Google Classroom, Edmodo, and WhatsApp. The purpose of carrying out this research is to describe the best media that is very easy to use for the continuity of the learning process. This type of research is a literature study by taking secondary data from several sources such as e-books, e-journals, websites, and other sources that are relevant to this research. Keywords: Learning Media, Online Learning, Covid-19, Education, Innovation